Temperature-Dependent Optical Properties of Liquid Water from 240 to 298 K - Rowe, P (Blackwell Publishing Ltd, 2020)
Clouds play a key role in Earth s radiative balance. Radiative transfer through liquid clouds depends on the optical properties of liquid water. Although these optical properties are known to be temperature dependent, radiative transfer simulations typically use properties based on measurements made at 298 K, even for supercooled liquid clouds at temperatures as low as 240 K. Here we report temperature-dependent complex refractive indices (CRIs) of liquid water at 240, 253, 263, and 273 K from 1 to 15,000 cm−1 (0.7 to 10,000 μm). Imaginary parts of the CRI (k) are inferred from values reported in the literature for temperatures of 238 to 298 K and the real parts are obtained via Kramers-Kronig transformation. Mie theory is used to calculate single scattering albedos and Legendre moments from the CRI, producing a set of optical constants suitable for radiative transfer calculations through supercooled liquid cloud at temperatures as low as 240 K. Ignoring the temperature dependence of complex refractive indices of liquid water is thereby found to result in biased-high supercooled liquid-cloud fluxes from 250 to 580 cm−1 and biased-low fluxes from 710 to 940 cm−1. ©2020. American Geophysical Union. All Rights Reserved.
Keywords: temperature-dependent complex refractive indices of liquid water; complex refractive index; liquid water; complex refractive indices of liquid water become more ice-like as temperature decreases to 240 K